2016
DOI: 10.1158/0008-5472.can-15-1439
|View full text |Cite
|
Sign up to set email alerts
|

STK11/LKB1 Deficiency Promotes Neutrophil Recruitment and Proinflammatory Cytokine Production to Suppress T-cell Activity in the Lung Tumor Microenvironment

Abstract: STK11/LKB1 is among the most commonly inactivated tumor suppressors in non-small cell lung cancer (NSCLC), especially in tumors harboring KRAS mutations. Many oncogenes promote immune escape, undermining the effectiveness of immunotherapies, but it is unclear whether inactivation of tumor suppressor genes such as STK11/LKB1 exert similar effects. In this study, we investigated the consequences of STK11/LKB1 loss on the immune microenvironment in a mouse model of KRAS-driven NSCLC. Genetic ablation of STK11/LKB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
403
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 472 publications
(433 citation statements)
references
References 39 publications
25
403
1
4
Order By: Relevance
“…An analysis exerted by Schabath et al on 442 tumors of lung adenocarcinoma patients confirmed the differential biological association of STK11 and TP53 in KRAS-mutant tumors (11). In line with these findings, our own preclinical analysis revealed that loss of the tumor suppressor Stk11/Lkb1 in Kras-mutated tumors induced marked changes within the tumor immune microenvironment in comparison to Kras-mutated tumors specified by accumulation of tumor-associated neutrophils, increased expression of T cell exhaustion markers, and secretion of tumor-promoting cytokines (12). Furthermore, these tumors were not responsive to αPD-1 blockade.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…An analysis exerted by Schabath et al on 442 tumors of lung adenocarcinoma patients confirmed the differential biological association of STK11 and TP53 in KRAS-mutant tumors (11). In line with these findings, our own preclinical analysis revealed that loss of the tumor suppressor Stk11/Lkb1 in Kras-mutated tumors induced marked changes within the tumor immune microenvironment in comparison to Kras-mutated tumors specified by accumulation of tumor-associated neutrophils, increased expression of T cell exhaustion markers, and secretion of tumor-promoting cytokines (12). Furthermore, these tumors were not responsive to αPD-1 blockade.…”
Section: Introductionsupporting
confidence: 80%
“…Despite careful intrathoracic application of Adeno-Cre and close clinical monitoring, we were unable to follow treatment response in these mice for longer periods due to rapid tumor growth. Mice treated with either RT or αPD-1 alone recapitulated our previously reported therapeutic responses and demonstrated significant inhibition or slowed tumor enlargement compared with naive tumors, respectively (8,12). The antitumor efficacy of RT was significantly better than PD-1 blockade in Kras/Lkb1 tumors.…”
Section: R E S E a R C H A R T I C L Esupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, LKB1 loss impaired the responses of KRAS mutant NSCLC to docetaxel monotherapy; the combination therapy of docetaxel and the MEK inhibitor selumetinib; or dual inhibition of the PI3K and MEK pathways (16,17). Additionally, LKB1 mutations were associated with the modulation of immune microenvironments, thus potentially impacting immunotherapeutic outcomes (18,19). The current data emphasize the need to determine tumor LKB1 status for patient stratification for evaluating therapeutic responses and identifying effective treatments.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, several reports have identified increased inflammatory signaling upon Lkb1 loss in different cell and tissue contexts, such as in skeletal muscle (12), macrophages (13), T cells (14), and lung cancer (15), implicating Lkb1 as a suppressor of inflammatory pathways. In PJS patients and in Lkb1 +/-mice, inhibition of cyclooxygenase-2 with the selective inhibitor celecoxib demonstrated partial efficiency in reducing PJS polyposis by reducing the size but not the number of tumors (16).…”
Section: Introductionmentioning
confidence: 99%